IMAGE LEADER: GENDER DIMENSION - Маленков, Є. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article studies the gender dimension of the process of forming the image of a political leader in modern conditions. Noted the need for modeling campaign political leader considering gender factor that influences the technologies and strategies of image formation and electoral behavior of citizens. The basic components and stages of the formation of the image of a political leader. Theoretical concepts, which examines gender issues.